Geomorphological connectivity and sensitivity examined in a recently degraded gravel-bed stream: implications for river-floodplain rehabilitation - Powell, Rebecca (Rhodes University, Faculty of Science, Department of Environmental Science, 2017)
The study of river complexity and sensitivity to future human land-use activities and climate change is a fast growing field within the discipline of fluvial geomorphology. Associated with this is a need to improve river rehabilitation and catchment management approach, design and effectiveness. This study aimed to investigate drivers of the recent geomorphological sensitivity of the Baviaanskloof River-floodplain, an upland system in South Africa, by integrating the concepts of geomorphological connectivity and Panarchy. The understanding generated was used to evaluate the approach of the State agency, Working for Wetlands (WfWet), to river-floodplain rehabilitation in the catchment.The concepts of geomorphological connectivity and Panarchy provide useful frameworks for understanding interactions between geomorphological processes and structure across scales of space and time. Geomorphological connectivity explains the degree to which water and sediment is linked in a river landscape, determined by the distribution of erosional and depositional landforms (Brierley et al. 2006; Fryirs et al. 2007a; Fryirs et al. 2007b). Panarchy attempts to explain lagged response to disturbances, non-linear interactions, and sudden shifts in system state, and has been applied largely to ecological systems. Panarchy theory, when combined with the concept of geomorphological connectivity, provides a guiding framework for understanding river complexity in greater depth. The first results chapter of this study investigated river long-term and recent geomorphological history, towards understanding the nature and timing of river geomorphological cycling between erosion and deposition. Optically Stimulated Luminescence dating of alluvial fan and floodplain sedimentary units was conducted, for analysis of river-floodplain long-term history (100s to 1 000s of years). Interviews with 11 local landowners, combined with analysis of historic aerial imagery and river-floodplain topographic surveys, provided a means of describing recent (last few decades) geomorphological dynamics. The results indicated that the Baviaanskloof is naturally a cut- and-fill landscape over scales of several hundred to thousands of years, characterized by the alternation between phases of high fluvial energy and alluvial fan expansion, and low energy conditions associated with floodplain accretion. Recent and widespread river-floodplain degradation was compressed into a short period of approximately 30 years, suggesting that one or more drivers have pushed the system beyond a threshold, resulting in increased water and sediment connectivity. The second results chapter investigated the role of human land-use activities and flooding frequency and magnitude, as drivers of recent river-floodplain degradation. Human impacts were investigated by describing land-use activities for the preceding 80 years, and relating these activities to changes in river-floodplain form and behavior. Temporal trends in flood events of different frequency and magnitude were investigated by analyzing rainfall data, integrated with landowner reports of flood-inducing rainfall magnitudes. The findings indicated that human land-use activities have been an important driver of recent river- floodplain degradation, through the enhancement of water and sediment connectivity across spatial scales of the catchment. Episodic and high magnitude floods synergized with human driven increased connectivity, precipitating stream power and geomorphological threshold breaches, resulting in a shift in river behaviour. The third results chapter investigated the influence of tributary-junction streams and fans on the geomorphological form, behavior and sensitivity of the Baviaanskloof River. Local- scale topographic impacts of tributary fans and streams were described using topographic surveys and geomorphological mapping techniques. Tributary streams form a major control on the behaviour of the river, by influencing the degree of coarse sediment connectivity with the main channel. Although tributary fans buffer the river from disturbances occurring in the wider catchment, they initiate topographic variations along the floodplain, influencing local-scale patterns of deposition and erosion along the river. The main river responds to water and sediment inputs from tributary junction streams by locally adjusting longitudinal slope, maintaining an overall constant slope of 0.0066 m/m. The response of the Baviaanskloof River to tributary junction fans and streams is however variable, and is fashioned by complex interactions between geomorphological and anthropogenic factors. The final two chapters of the thesis evaluate the findings of the study within the context of river-floodplain rehabilitation approaches in South Africa, and within the theoretical, philosophical and methodological context of the research. The first of these two chapters evaluates the approach of the WfWet programme to river-floodplain rehabilitation in the Baviaanskloof. The chapter indicates that the present practice of WfWet is to reinstate a pre-degradation state, which is not suited to the Baviaanskloof River-floodplain, since the river-floodplain has passed a geomorphological threshold, resulting in a new set of interacting processes and landforms. The author presents a conceptual model illustrating the existence of geomorphological adaptive cycles interacting across spatial and temporal scales, thereby attempting to explain a river Panarchy specific to the Baviaanskloof. From this conceptual model, a hierarchical rehabilitation framework, targeting geomorphological processes and structure situated at different spatial and temporal scales of the landscape is suggested. The final chapter discusses the implications of integrating the concepts of geomorphological connectivity and river Panarchy theory in studies of river complexity and sensitivity to geomorphological change. The author suggests that there is scope for further investigation of the application of the two concepts within the discipline of fluvial geomorphology, particularly with regard to developing quantitative approaches to measuring and describing connectivity and Panarchy.
Keywords: Uncatalogued